Cooperating teachers’ mentoring moves during internship of early childhood pre-service teachers - Calamlam, Josephine Mallari; Mokshein, Siti Eshah (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2019)
Understanding the mentoring practices used by cooperating teachers to guide and support early childhood (EC) pre-service teachers’ learning-to-teach during internship (or practicum) in a disadvantaged environment was the main purpose of this qualitative case study. Three EC pre-service teachers and their cooperating teachers were purposively selected from which data was collected through interviews, documents, classroom observations, and post conferences. Collected data were analyzed and through the analyses were identified cooperating teachers’ appropriate mentoring behaviors and practices. These mentoring behaviors and practices formed the themes which was used as a ‘mentoring framework’ during internship. The findings presented in this study has implications towards the development of mentoring, and the developed framework will serve as a guide towards the development of cooperating teachers’ capability for effective mentoring.